(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine and analyze the implementation of Article 13 paragraph 1 and 2 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 13 of 2017 concerning Block and Confiscation Procedures. Then to find out and analyze what are the obstacles faced by the Makassar City National Land Agency in Implementing Article 13 paragraphs 1 and 2 of the Regulation of the Minister of Agrarian and Spatial Planning Number 13 of 2017 concerning Procedures for Blocking and Confiscation. This study uses a research method, with the type of juridical empirical research. The types and sources of data used in this study are primary data and secondary data. To get the required data, the researcher collected data through three collection methods, namely interviews, observation, and documentation. And the data obtained, both primary and secondary legal materials, were analyzed qualitatively and then presented descriptively. Abstrak Penelitian ini bertujuan untuk Untuk mengetahui dan menganalisis pelaksanaan Pasal 13 ayat 1 dan 2 Peraturan Menteri Agraria Dan Tata Ruang Nomor 13 Tahun 2017 tentang Tata Cara Blokir dan Sita. Kemudian Untuk mengetahui dan menganalisis apa saja hambatan yang dihadapi oleh Badan Pertanahan Nasional Kota Makassar dalam Mengimplementasikan Pasal 13 ayat 1 dan 2 Peraturan Menteri Agraria Dan Tata Ruang Nomor 13 Tahun 2017 tentang Tata Cara Blokir dan Sita. Penelitian ini menggunakan metode penelitian, dengan tipe Penelitian Yuridis Empiris, Adapun jenis dan sumber data yang dipergunakan dalam penelitian ini adalah Data Primer dan Dat Sekunder. Untuk mendapatkan data yang dibutuhkan Peneliti mengumpulkan data melalui tiga metode pengumpulan yaitu Wawancara, Observasi, dan Dokumentasi. Dan data yang diperoleh baik bahan hukum primer maupun sekunder dianalisis secara kualitatif kemudian disajikan secara deskriptif.